Canine intraneural perineurioma - Martins, Tessie B.; Ramos, Adriano T.; Viott, Aline de M.; Adeodato, Alex G.; Graça, Dominguita L. (Brazilian Journal of Veterinary Pathology, 2010)
Perineuriomas are slow growing tumors, exclusively compound of well-differentiated perineurial cells. They are rare in human and canine. A dog was submitted to necropsy with a clinical diagnosis of myelin sheath tumor in the brachial plexus area. Slides of the tumor were treated with histochemistry and immunohistochemistry techniches and the diagnostic of perineurioma intraneural was established.